Research governance review of a negligible-risk research project: Too much of a good thing?. (July 2018) - Rush, Amanda; Ling, Rod; Carpenter, Jane E; Carter, Candace; Searles, Andrew; Byrne, Jennifer A
There are increasing concerns that research regulatory requirements exceed those required to manage risks, particularly for low- and negligible-risk research projects. In particular, inconsistent documentation requirements across research sites can delay the conduct of multi-site projects. For a one-year, negligible-risk project examining biobank operations conducted at three separate Australian institutions, we found that the researcher time required to meet regulatory requirements was eight times greater than that required for the approved research activity (60 hours versus 7.5 hours respectively). In total, 76 business days (almost four months) were required to obtain the necessary approvals, and site-specific processes required twice as long (52 business days/approximately 10 weeks) as primary Human Research Ethics Committee and Research Governance Office processes (24 business days/ approximately five weeks). We describe the impact of this administrative load on the conduct of a one-year, externally-funded research project, and identify a shared set of application requirements that could be used to streamline and harmonise research governance review of low- and negligible-risk research projects.